A Comparison of the handwriting speed among 3rd grade primary school students - Rozi Zeinali; Maedeh Sabagh Turkan; Atiyeh Javantash; Navid Mirzakhani (Shahid Beheshti University of Medical Sciences, 2013)
Background and Aim: Handwriting is an important functional task frequently used in all grades beginning in kindergarten .Children are expected to acquire a level of handwriting proficiency that enables them to make skillful use of handwriting as a tool to carry out their work at school. So handwriting fluency in a written examination requires the writer to maintain sufficient speed. The aim of the study was to examine and compare the speed of hand writing skills between girls and boys students.Material and Method: This Discriptive analytic survey with the technique of cluster sampling was carried out on the 2 sample schools on the areas of two & sixth in great Tehran in 1386-7(s.y).The outcome of measurement were the "speed of copying'' and "writing of memorized poem". The subjects included 315 students (193 female, 122 male) of which were 18 left handed girls and 12 left handed boys. Result : The results of this study revealed that the speed of writing of copying was 37/05 words/min ,while the speed of writing a memorized poem was 31/1 words/min in the girls and boys students.Conclusion: There were no significant differences between the speed of hand writing among boys and girls and also between Right & Left handed students. However being left or right handed is an important factor in poem memorizing and right handed were faster than left handed.